Does the presence of a urinary catheter predict severe sepsis in a bacteraemic cohort?. Issue 4 (April 2017) - Melzer, M.; Welch, C.
Summary: Background: Sepsis is a major cause of mortality with an estimated 37, 000 deaths in the UK each year. This study aimed to determine host factors that can predict severe sepsis in a bacteraemic cohort. Methods: From December 2012 to November 2013, demographic, clinical and microbiological data were collected on consecutive patients with bacteraemia at a London teaching hospital. These data were used to categorize patients as having severe or non-severe sepsis. Multi-variate logistic regression was used to determine the association between host factors and severe sepsis. Findings: Five hundred and ninety-four bacteraemic episodes occurred in 500 patients. The majority of cases were in patients aged >50 years (382/594, 64.3%) and in males (346/594, 58.2%). The most common isolates were Escherichia coli (207/594, 34.8%) and meticillin-susceptible Staphylococcus aureus (57/594, 9.6%). In logistic regression multi-variable analysis, site of infection was significantly associated with severe sepsis. For catheter-associated urinary tract infections, the association was significant after adjustment for age, sex, Charlson comorbidity index and where infection was acquired (odds ratio 3.94, 95% confidence interval 1.70–9.11). Conclusions: Urinary catheters increase the risk of severe sepsis. They should only be used if clinically indicated. If inserted, a care bundle approach should be used and the anticipated removal date should be recorded unless a long-term catheter is required. In the context of sepsis, the presence of a urinary catheter should prompt immediate implementation of 'Sepsis Six' and consideration of transfer to a critical care unit.